Re-treating the office empire: Henri Michaux's Par des Traits and the coming barbarism. Issue 2 (1st February 2021) - Üstün, Berkay
ABSTRACT: In this study I discuss one of Henri Michaux's last works Par des Traits, paying close attention to the way an overtly political critique informs the adventurous graphic experiments involved in the work. Contextually, I situate Michaux's utopian discourse about a new bio-historical 'function' created by a new sign within the larger plan of his earlier preoccupations with physiologically provoked anomalies and techniques of contemplation, tracing his move from individual forms of semiotic apprenticeship to more collective concerns like the environmental degradations and catastrophes caused by the human species in the last quarter of the 20th century. In arguing for the relevance of the concept of 'real subsumption' to the litany of grievances Michaux addresses in his text, I situate Michaux's Par Des Traits in a field of discourse shared by historical materialism's own deep historical currents (Kluge and Negt) as well as other semiotically minded critiques of capitalism, as found in Félix Guattari's work.